PENGARUH PELAKSANAAN PENDIDIKAN PROFESI GURU (PPG) DALAM JABATAN DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI PROVINSI LAMPUNG - Rido Yusuf Abadi, - (2023)
This study aims to obtain a complete picture of the effect of the implementation of PPG in position and the principal's leadership style on teacher performance in Lampung Province. The research method used is a descriptive quantitative method, namely making a description of a situation objectively using numbers. The population of this study were teachers who had passed PPG periods 3 and 4 in 2022 in Lampung province. Data were collected using a Likert scale-based questionnaire and analyzed using simple linear regression analysis, multiple linear regression analysis, and path analysis. The results showed that there was a significant effect of the implementation of in-service PPG on teacher performance at school, there was a significant effect of the principal's leadership style on teacher performance at school, and there was a significant effect between the implementation of in-service PPG and the principal's leadership style on teacher performance at school. As conclution, it is important for school principals to apply a good leadership style and facilitate teachers who will carry out PPG in position in order to improve the ability and experience of teachers in educating and teaching students. This study provides recommendations for principals and teachers to continue to improve their capacity to create good performance that can improve the quality of education in schools.